De olho no Big Brother Brasil: a performance mediada pela TV - Joana de Almeida Meniconi (2005)
The present work has, as its main objective, the observation of the way through which the participants of a reality show create characters for themselves and perform them to the cameras, thus reaching a wider audience with whom they do not establish direct contact. In order to draw reasonable conclusions from the proposed object, we discussed some concepts and notions that turned out to be fundamental to the empiric analysis undertaken, such as television, mediation and social representations. We tried to understand television as a privileged arena to observe the dynamics of social representations and came to the conclusion that the genres and formats of television shows can be classified through the reoccurance of certain representational patterns. Therefore, we used the notion of reality show as a television genre in itself and Big Brother Brasil as the format chosen, since the show seemed to be the one that best portrayed, at the time, the performances directed to the cameras. The participants of television shows like BBB, in order to succeed in their auto-performances, have to work with at least three types of interaction: those with the other participants, strongly influenced by the confinement and by the game proposed; those with the producers and the show host and, finally; those with the audience, mediated by the cameras. Once we put these three types of interactions in a proper scheme, we could establish our analytic corpus: thirteen episodes from the third season of BBB in which we watched more closely the participants, their performances and the effectiveness of the performances of six specific participants.